Perianal Paget's Disease Metachronically Associated with Adenocarcinoma - Chiquetti, Camila Vieira; Gonçalves, Victor Hugo de Araújo; Uliana, Leonardo Carnielli; Ribeiro, Carlos Otávio da Silva; Fonseca, Odinilson Almeida; Santos, Carlos Henrique Marques dos; Takita, Luiz Carlos (Journal of Coloproctology, 2024)
Introduction This article describes an unusual case of perianal Paget's Disease in a 42-year-old man, highlighting distinct characteristics about more typical cases.Case report 42-year-old male patient with persistent perianal lesion, recurrent abscesses, and discomfort. Magnetic resonance imaging indicated a possible fistulous path. Biopsy revealed secondary anal Paget's disease and adenocarcinoma. Chemotherapy and radiotherapy treatment demonstrated a positive response.Discussion Perianal Paget's Disease is a rare condition of the anal canal that is part of the Extramammary Paget's Disease (EMPD) group. Symptoms include itching, pain, perianal bleeding, and skin lesions. Diagnosis can be challenging and usually involves performing a histopathological biopsy associated with an immunohistochemical study. Treatment varies and may involve surgery, radiotherapy, and chemotherapy. Due to the rarity of the disease, the best therapeutic approach is not yet well defined, and follow-up is essential due to the risk of recurrence.Conclusion Perianal Paget's Disease is rare and requires differentiation from other conditions. Early detection is essential to prevent malignancy.
Keywords: Extramammary Paget's Disease; rectal fistula; Diseases of the Anus; anal channel